Novel Conserved-region T-cell Mosaic Vaccine With High Global HIV-1 Coverage Is Recognized by Protective Responses in Untreated Infection - Ondondo, Beatrice (Mol Ther, 2016)
An effective human immunodeficiency virus type 1 (HIV-1) vaccine is the best solution for halting the acquired immune deficiency syndrome epidemic. Here, we describe the design and preclinical immunogenicity of T-cell vaccine expressing novel immunogens tHIVconsvX, vectored by DNA, simian (chimpanzee) adenovirus, and poxvirus modified vaccinia virus Ankara (MVA), a combination highly immunogenic in humans. The tHIVconsvX immunogens combine the three leading strategies for elicitation of effective CD8(+) T cells: use of regions of HIV-1 proteins functionally conserved across all M group viruses (to make HIV-1 escape costly on viral fitness), inclusion of bivalent complementary mosaic immunogens (to maximize global epitope matching and breadth of responses, and block common escape paths), and inclusion of epitopes known to be associated with low viral load in infected untreated people (to induce field-proven protective responses). tHIVconsvX was highly immunogenic in two strains of mice. Furthermore, the magnitude and breadth of CD8(+) T-cell responses to tHIVconsvX-derived peptides in treatment-naive HIV-1(+) patients significantly correlated with high CD4(+) T-cell count and low viral load. Overall, the tHIVconsvX design, combining the mosaic and conserved-region approaches, provides an indisputably better coverage of global HIV-1 variants than previous T-cell vaccines. These immunogens delivered in a highly immunogenic framework of adenovirus prime and MVA boost are ready for clinical development.